Polymerization of 4-Methylpentene -1- by the MgCl2|Eb|TiCl4|Al(iBu)3 Catalyst System 1. Kinetic Investigations - M. A. Abu-Eid; P. J. Tait (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The kinetics of the polymerization of 4-methylpentcne-1- with the MgC12|EB|Ticl4|Al(iBu)3 catalyst systems have been investigated. The conditions and requirements to achieve the highest activity and stereospecificity of the MgC12-supported catalyst systems were discussed. Moreover, the role of aluminum alkyl and ethyl benzoate on the activity and stereo-regularity of the polymers have been reported.